EFL STUDENTS' PERCEPTIONS OF ENGLISH CONVERSATION VIDEO ON INSTAGRAM REELS IN THEIR SPEAKING PRACTICE - Ganita, Rahmawati; Setia Muljanto; Yustika Nur Fajriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explored EFL students’ perceptions of English conversation videos on Instagram Reels in their speaking practice. Using a qualitative descriptive design, the study involved seven English Education students selected through purposive sampling from 44 questionnaire respondents. Data were collected through semi-structured interviews and analyzed thematically. The findings revealed that students perceived English conversation videos positively as both entertaining and educational. Participants reported that the videos provided authentic exposure to pronunciation, vocabulary, expressions, slang, and daily conversations. The videos also encouraged speaking practice through imitation, repetition, and the use of newly learned expressions in real-life communication. Frequent exposure helped students become more familiar with spoken English and increased their confidence in speaking. Although some participants experienced difficulties related to unfamiliar accents, fast speech, and new expressions, these challenges did not diminish their overall positive perceptions. The study concludes that English conversation videos on Instagram Reels are valuable informal learning resources that support EFL students’ speaking practice through authentic and engaging language exposure.